PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS MODUL APLIKASI SMARTPHONE PADA MATA KULIAH PENGELOHAN MAKANAN NUSANTARA DI JURUSAN PKK FT UNM - Haeril; Nahriana; Abdul Muis Mapalotteng (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2021)
This research aims to; (1) knowing the stages of development learning media based on smartphone application modul in Indonesian food processing courses; (2) find out that the learning media based on the smartphone application modul that was developed meets the valid, effective and practical criteriaThis research method is Research and Development with ADDIE development model. The research subjects were 20 students and 1 lecturer from the PKK FT UNM Department. Data collection through documentation, observation and questionnaire methods were analyzed using quantitative descriptive statistical techniques. The results of the research on development learning media based on smartphone application modul through the following stages: (1) analyzing the initial conditions and learning needs; (2) the design stage of designing learning devices and media; (3) making lesson plans, modul, recipes for side dishes, learning media based on smartphone application modul and guide books, as well as data collection instruments that go through a validation stage by material experts and media experts; (4) product implementation in individual trials, small group trials and field trials after minor revisions; (5) stages of summative evaluation and product finalization. The quality of the learning media was declared very valid by the media expert validator with a value of97.22%and material expert with value95.14%. The practicality of the media based on the observation of student activities scores90.76% and activities of lecturers get grades 95.81% criteria are very active, and student response questionnaires get a score of 90.32% criteria are very good. Effectiveness is stated based on the results of the learning test obtaining an average value of 86.46% and the performance assessment obtaining an average of 85.45% where all students are declared to have passed, so that the learning media based on the smartphone application modul is suitable for use in Indonesian food processing courses in the Department of Education PKK FT UNM.